PROJECTIVE-RASTER METHODS OF REGISTRATION OF SECTIONS OF SURFACE OF LOCAL OBJECTS - Belous, V.; Bodnar, C. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
In work is solved the problem of visualizing terrain contour lines on the surface of the volume bodies. Modern methods and means of digital photogrammetry represent a real opportunity to return to the previously known analog methods of visualization, real-time monitoring, analysis and evaluation of the surface shape of the local volume bodies. the Essence of these methods consists in designing a linear raster digital projector or laser light plane on the object and the real-time monitoring and, if necessary, photographing localized on the family member contour and processing using modern software and hardware and digital technology. This technique was used quite successfully in the study of local objects of small size in many application areas of applied photogrammetry: architecture and construction, studying of monuments of historical and cultural heritage, ship, air, auto, construction, medicine, etc. the paper presents circuits and analysis of their application with the shooting design of linear raster parallel beam by moving the light plane, the Central design of the raster, the mathematical apparatus of calculation of parameters of acquisition and the results of the survey of the surface of the cone, the blades, and sculptures. The generalized formulas allow you to select the shooting options of objects to perform calculations and get the dimensions and a graphical model of the contour surfaces. This article is intended for students and teachers in the field of knowledge Architecture and engineering and professionals working in the field of application of modern methods of applied photogrammetry.